Barriers and opportunities for the treatment of mild-to-moderate depression with a watchful waiting approach. Issue 3 (March 2021) - Iglesias-González, M.; Gil-Girbau, M.; Peñarrubia-María, M.T.; Blanco-García, E.; Fernández-Vergel, R.; Serrano-Blanco, A.; Carbonell-Duacastella, C.; Alonso, J.; Rubio-Valera, M.
Highlights: General practitioners report difficulties in diagnosing and treating depression. Adequate bond of trust with patients facilitates depression management. Structural support in primary care may prevent overprescription of antidepressants. Psychiatrists should reconsider their role when managing depression in primary care. Abstract: Objective: The aim of this study is to explore barriers and opportunities in non-pharmacological treatment of depression in primary care (PC) from the perspective of family physicians (FPs). Methods: Qualitative analysis was used to explore a sample of 36 FPs treating patients with depressive symptoms. Criteria to maximize variability were followed. Participants were identified by key informants. Six group interviews were developed following a semi-structured thematic script. All interviews were transcribed, analyzed and triangulated. Information was saturated. Principals of reflexivity and circularity were implemented. Results: The results obtained followed 3 main theoretical axes: the FP, the patient, the healthcare system, and the interaction between them. Barriers included poor alignment with clinical practice guidelines, inadequate FP training, patients' preferences and structural challenges in PC. Among opportunities were good FP clinical interview skills, the beneficial bond of trust between patients and FPs and improved communication with mental healthcare services. Conclusion: Based on FPs' perceptions, non-pharmacological treatment of depression in PC is particularly limited by lack of structured training; patients' preferences and treatment expectations; structural challenges in PC; and insufficient support from specialized mental health professionals. Practice implications: Resources for education, structural support in PC and modified back up from mental healthcare services are needed.